Caesarean Section in the Perspective of Family, Health, and Islamic Law - Beddu, Muhammad Juni; Yanti, Novi; Noviyanti, Noviyanti; Aslina, Neri; Daud, Normadiah (AL-ISTINBATH : Jurnal Hukum Islam, 2024)
This research explores the complexities of cesarean section in the context of family, health, and Islamic law. The main objective is to understand the views and experiences of Muslim families regarding cesarean sections, as well as analyze the health impacts and legal implications associated with them. The research enriches understanding of the role of cesarean section in Muslim communities, provides comprehensive insight into aspects of family, health, and Islamic law, and offers a framework to support informed decision-making in medical practice and health care policy. This study uses qualitative methods in describing family perspectives, Islamic health, and legal aspects regarding cesarean sections. The research approach used is a legal and sociological approach. The analysis method used is content analysis to explore family perspectives, Islamic health, and legal aspects regarding cesarean sections. The findings reveal a range of perspectives among Muslim families regarding caesarean sections, with health and safety considerations being major factors in decision-making. The health impact of cesarean section on mother and baby, including risks and benefits, is also examined in depth. In Islamic law, caesarean section is permitted if necessary, to protect the life of the mother or baby. Ethical and clinical recommendations should reflect relevant religious values and views. To make a decision regarding a cesarean section, it is important to consider a variety of factors, including family views, aspects of health, and Islamic law.